Lead-free piezoelectric composition, piezoelectric element, and device
Patent Information
- Application Number
- KR1020257041468
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-02
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2044-08-02
Smart Images

Figure R1020257041468_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to a lead-free piezoelectric composition, a piezoelectric element, and an apparatus. Background Technology
[0002] Conventionally, PZT-based (lead zirconate titanate-based) compositions have been widely used as compositions exhibiting piezoelectricity, but there is a demand for the development of lead-free piezoelectric compositions that do not use lead to reduce environmental burden. As a candidate for such lead-free piezoelectric compositions, for example, alkali niobate-based perovskite oxides have been proposed. However, alkali niobate-based perovskite oxides have a problem in that their sinterability may be insufficient.
[0003] As a configuration for increasing the sinterability of alkali niobate-based perovskite oxides, a configuration is proposed in which, in a lead-free piezoelectric composition, a phase composed of another type of oxide is formed in addition to a main phase composed of alkali niobate-based perovskite oxides (see, for example, Patent Documents 1 to 4). Specifically, Patent Document 1 discloses a configuration for forming a phase comprising an M-Ti-O-based spinel compound (wherein element M is an element of 1 to 4 valence). Furthermore, Patent Document 2 discloses a configuration for forming a phase comprising a spinel compound represented as (M4, Ti)O4 (wherein the metal element M4 is one or more of Fe, Co, and Zn). Furthermore, Patent Document 3 discloses a configuration for forming a phase comprising a spinel compound containing Ti. Furthermore, Patent Document 4 describes compositional formula A2 1-x Ti 1-x Nb 1+xA configuration is disclosed in which a phase is formed from one of the oxides represented by O5 (wherein element A2 is at least one of alkali metals and satisfies 0 ≤ x ≤ 0.15) and the oxide represented by the compositional formula A3Ti3NbO9 (wherein element A3 is at least one of alkali metals). Prior art literature
[0004] Japanese Patent Publication No. 5715309, Japanese Patent Publication No. 6895845, International Publication No. 2022 / 215666, International Publication No. 2023 / 026614 The problem to be solved
[0005] In such piezoelectric compositions, it is required to increase the mechanical quality factor Qm and reduce the dielectric loss (dielectric loss tangent) tanδ, which is the reciprocal of the mechanical quality factor Qm. The mechanical quality factor Qm is a parameter that indicates the sharpness of the resonance spectrum of a piezoelectric element, and by increasing the mechanical quality factor Qm, it becomes possible to effectively vibrate the piezoelectric element. However, the mechanical quality factor Qm and dielectric loss tanδ in lead-free piezoelectric compositions have not been sufficiently examined, and further improvement of the mechanical quality factor Qm and further reduction of the dielectric loss tanδ have been desired. means of solving the problem
[0006] The present disclosure can be realized in the following forms.
[0007] [1] According to one embodiment of the present disclosure, a lead-free piezoelectric composition is provided. The lead-free piezoelectric composition comprises a column made of an alkaline niobate perovskite oxide and a float having a tungsten bronze-type structure comprising at least one of niobium (Nb) and a compound selected from at least one of barium (Ba), calcium (Ca), strontium (Sr), sodium (Na), and potassium (K), and the float satisfies at least one of the three conditions shown in the following (1)-(3) regarding the cumulative frequency of 80% particle size (D80), 50% particle size (D50), and 20% particle size (D20) in the volume-based particle size distribution.
[0008]
[0009] According to this type of lead-free piezoelectric composition, in a lead-free piezoelectric composition having a column made of alkaline niobate perovskite oxide, at least one of the three conditions shown in equations (1) to (3) above is satisfied with respect to the particle size of the float containing a compound having a tungsten bronze-type structure, thereby increasing the mechanical quality factor Qm in the lead-free piezoelectric composition and reducing the dielectric loss tanδ.
[0010] [2] In the above-mentioned lead-free piezoelectric composition, the cumulative frequency 80% particle size (D80) in the volume-based particle size distribution may satisfy the above equation (1) and also satisfy the following equation (4).
[0011]
[0012] With such a configuration, the mechanical quality factor Qm in the lead-free piezoelectric composition can be increased, and the effect of reducing dielectric loss tanδ can be further enhanced.
[0013] [3] In the above-mentioned lead-free piezoelectric composition, the cumulative frequency 50% particle size (D50) in the volume-based particle size distribution may satisfy the above (2) equation and also satisfy the following (5) equation.
[0014]
[0015] With such a configuration, the mechanical quality factor Qm in the lead-free piezoelectric composition can be increased, and the effect of reducing dielectric loss tanδ can be further enhanced.
[0016] [4] In the above-mentioned lead-free piezoelectric composition, the cumulative frequency 20% particle size (D20) in the volume-based particle size distribution may satisfy the above (3) equation and also satisfy the following (6) equation.
[0017]
[0018] With such a configuration, the mechanical quality factor Qm in the lead-free piezoelectric composition can be increased, and the effect of reducing dielectric loss tanδ can be further enhanced.
[0019] [5] In the above-mentioned lead-free piezoelectric composition, the niobate alkali perovskite-type oxide constituting the main phase may contain manganese (Mn). With such a composition, the mechanical quality factor Qm in the lead-free piezoelectric composition can be increased, and the effect of reducing dielectric loss tanδ can be further enhanced.
[0020] [6] In the above-mentioned lead-free piezoelectric composition, the niobate alkali perovskite-type oxide constituting the main phase is of the compositional formula (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 )O 3+e(However, element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, and Sr, element M2 is at least one of Ti and Zr, 0<a<1, 0<b<1, a+b=1, c satisfies 0.80<c<1.10, 0<d1<1, 0<d2<1, 0<d3<1, d1+d2+d3=1, and e is a value indicating oxygen deficiency or excess) may be included in a columnar phase composed of an alkali niobate perovskite-type oxide, satisfying b / (d2+d3)>1.0. With such a composition, the mechanical quality factor Qm in the lead-free piezoelectric composition can be increased, and the effect of reducing dielectric loss tanδ can be further enhanced.
[0021] [7] According to another embodiment of the present disclosure, a piezoelectric element is provided having a piezoelectric body formed by a lead-free piezoelectric composition as described in any one of claims [1] to [6] and an electrode mounted on the piezoelectric body.
[0022] According to this type of piezoelectric element, the piezoelectric performance can be improved because it is equipped with a piezoelectric material formed from a lead-free piezoelectric composition in which the dielectric loss tanδ is reduced along with an increased mechanical quality factor Qm.
[0023] [8] According to another form of the present disclosure, a device having a piezoelectric element as described in [7] is provided.
[0024] According to this type of device, the overall performance of the device can be improved because it is equipped with a piezoelectric element having a lead-free piezoelectric composition with reduced dielectric loss tanδ and an increased mechanical quality factor Qm.
[0025] The present disclosure can be realized in various forms, for example, in the form of a lead-free piezoelectric composition, a piezoelectric element using the same, various devices equipped with a piezoelectric element (knock sensor, ultrasonic vibrator, cutting tool, ultrasonic sensor, actuator, etc.), and a method for manufacturing a lead-free piezoelectric composition. Brief explanation of the drawing
[0026] FIG. 1 is a perspective view showing the external appearance of a piezoelectric element. Figure 2 is a flowchart showing an example of a method for manufacturing a piezoelectric element. Figure 3 is a schematic diagram showing an ultrasonic scalpel as an example of a device. Figure 4 is a schematic diagram showing an ultrasonic scaler as an example of a device. FIG. 5 is a schematic diagram showing an ultrasonic cleaner as an example of a device. FIG. 6 is a schematic diagram showing an ultrasonic processing machine as an example of a device. FIG. 7 is a schematic diagram showing a piezoelectric transducer as an example of a device. FIG. 8 is a schematic diagram showing an ultrasonic motor as an example of a device. FIG. 9 is a schematic diagram showing a piezoelectric gyro sensor as an example of a device. FIG. 10 is a schematic diagram showing a stacked piezoelectric filter as an example of a device. FIG. 11 is a schematic diagram of a knock sensor as an example of a device. Figure 12 is an explanatory diagram summarizing the composition and evaluation results of each sample. Figure 13 is an explanatory diagram summarizing the composition and evaluation results of each sample. Figure 14 is an explanatory diagram summarizing the composition and evaluation results of each sample. Figure 15 is an explanatory diagram showing the composition of the main phase of each sample. Figure 16 is an explanatory diagram regarding the buoyancy plastic component for forming the buoyancy of each sample. Specific details for implementing the invention
[0027] A. Lead-free piezoelectric composition:
[0028] The lead-free piezoelectric composition of the present embodiment comprises a column made of an alkaline niobate perovskite oxide and a float comprising a compound having a tungsten bronze-type structure including at least one selected from niobium (Nb), barium (Ba), calcium (Ca), strontium (Sr), sodium (Na), and potassium (K). The float satisfies at least one of the three conditions shown in the following equations (1) to (3) regarding the cumulative frequency of 80% particle size (D80), 50% particle size (D50), and 20% particle size (D20) in the volume-based particle size distribution.
[0029]
[0030] (A-1) About the main pillar :
[0031] The alkaline niobate perovskite oxide constituting the column preferably includes at least one of alkali metals (potassium (K), sodium (Na), lithium (Li), etc.) as an alkaline component, and particularly preferably includes at least one of potassium (K) and sodium (Na). In addition, the alkaline niobate perovskite oxide constituting the column may include at least one of alkaline earth metals (calcium (Ca), strontium (Sr), barium (Ba), etc.) as an alkaline component.
[0032] The alkali niobate perovskite-type oxide constituting such a columnar phase may contain manganese (Mn). It is believed that the mechanical quality factor Qm is improved by the solid solution of manganese (Mn) as an acceptor at the niobium site (the B site of the perovskite-type crystal structure).
[0033] In addition, the alkali niobate perovskite oxide constituting the main body is preferably an alkali niobate perovskite-type oxide satisfying the following composition formula (7).
[0034]
[0035] However, in the formula, element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, and Sr, element M2 is at least one of Ti and Zr, 0<a<1, 0<b<1, a+b=1, c satisfies 0.80<c<1.10, 0<d1<1, 0<d2<1, 0<d3<1, d1+d2+d3=1, e is a value representing oxygen deficiency or excess, and b / (d2+d3)>1.0.
[0036] In the above composition formula (7), elements A1 and M1 are placed at the A site of the perovskite structure, and Nb (niobium), Mn (manganese), and element M2 are placed at the B site. Among the combinations of values for which a to e of the above composition formula (7) are formed, values that are desirable from the perspective of the electrical properties or piezoelectric properties of the lead-free piezoelectric composition are selected from the described range. In the niobate alkali-based perovskite oxide shown in composition formula (7), a=0 (composition not containing alkali metals), b=0 (composition not containing any of Ca, Sr, or Ba), d1=0 (composition not containing Nb), d2=0 (composition not containing Mn), and d3=0 (composition not containing any of Ti or Zr) are excluded.
[0037] Among the oxygen coefficients 3+e, the coefficient e is a positive or negative value indicating a deficiency or excess of oxygen relative to the oxygen coefficient, which is typically 3. The oxygen coefficient (3+e) can take a value in which the columnar phase constitutes a perovskite oxide. A typical value for the coefficient e is e=0, and -0.1 ≤ e ≤ 0.1 is preferred. Additionally, the value of the coefficient e can be calculated from the electrical neutral conditions of the columnar phase composition. However, for the columnar phase composition, a composition that deviates slightly from electrical neutral conditions may also be permitted.
[0038] In the above composition formula (7), the coefficients b, d2, and d3 satisfy "b / (d2+d3) > 1.0" as described above, thereby increasing the mechanical quality factor Qm of the lead-free piezoelectric composition. The reason for this is presumed to be as follows. That is, it is believed that the mechanical quality factor Qm is improved by Mn being dissolved as an acceptor at the sites of Nb. However, Mn is difficult to dissolve in niobate alkali perovskite-type oxides and is prone to segregation as an anomaly in the lead-free piezoelectric composition. It is believed that the ease of dissolution depends on the ionic radius or valence of the metal atoms being dissolved, and it is thought that trivalent Mn is difficult to dissolve in the B sites, where pentavalent Nb is mainly located. On the other hand, divalent elements Ba, Ca, and Sr are easily dissolved in the A sites, where monovalent alkali metals are located. In addition, it is presumed that the appropriate amount of Ba, Ca, and Sr, which are close to Mn in terms of valence, is incorporated at site A, which helps Mn to be incorporated at site B. It is thought that by adjusting the compositional ratio of Mn to Ba, Ca, and Sr so that “b / (d2+d3) > 1.0”, an appropriate amount of Mn is incorporated at site B, and the mechanical quality factor Qm is improved. Although there is no specific limit to the upper limit of “b / (d2+d3)”, it is preferable that “b / (d2+d3) ≤ 2.0”.
[0039] (A-2) Regarding the injury:
[0040] The lead-free piezoelectric composition of the present embodiment comprises, as described, a compound having a tungsten bronze-type structure comprising at least one selected from niobium (Nb) and barium (Ba), calcium (Ca), strontium (Sr), sodium (Na), and potassium (K). Here, the compound having a tungsten bronze-type structure is a compound represented by the following formula (8).
[0041]
[0042] However, in the formula, A contains two or more elements of 1 to 2 valence, and B contains one or more elements of 2 to 5 valence. Also, regarding k, l, and δ, k=3, l=5, and δ=0, respectively, are the standard values; however, as long as the tungsten bronze-type crystal structure can be maintained and changes in the properties of the compound can be allowed, the values may deviate from the standard values and may also contain impurity elements. Specific examples of compounds represented by the above formula (8) include, for example, Ba3Nb5O 15 , Ba2KNb5O 15 , Ba2NaNb5O 15 Examples include the above. In addition, if the degree to which the characteristics of the float change due to the inclusion of a compound having a tungsten bronze-type crystal structure is within an acceptable range, other types of compounds, such as spinel compounds, may be mixed in.
[0043] The compound having a tungsten bronze-type structure constituting the above-mentioned phase does not possess piezoelectric properties, but by being mixed with a columnar phase composed of alkali niobate perovskite oxide, it improves the sinterability of the piezoelectric composition and its structural stability, as well as improves the piezoelectric properties. From the perspective of securing the effect of increasing the sinterability of the lead-free piezoelectric composition, it is preferable that the content ratio of the phase be 0.3 volume% or more, and more preferable that it be 0.5 volume% or more. Furthermore, from the perspective of securing the piezoelectric properties of the lead-free piezoelectric composition, it is preferable that the content ratio of the phase be 10 volume% or less, and more preferable that it be 7 volume% or less. In addition, whether the compound constituting the phase is a compound having a tungsten bronze-type structure can be determined by performing Rietveld analysis using the diffraction results of powder X-ray diffraction (XRD).
[0044] In addition, the float of the lead-free piezoelectric composition of the present embodiment satisfies at least one of the three conditions shown in the following equations (1) to (3) regarding the cumulative frequency of 80% particle size (D80), 50% particle size (D50), and 20% particle size (D20) in the particle size distribution based on volume, as described above.
[0045]
[0046] In addition, when obtaining the above-mentioned D80, D50, and D20, the sintered body of the target lead-free piezoelectric composition is mirror-polished and subjected to conductive treatment, and then a reflected electron image is captured at 500 to 3000x magnification using an electron probe / micro analyzer (EPMA). At this time, the obtained reflected electron image is binarized using image analysis software to classify it into a columnar phase and a floating phase. Then, the particle diameter equivalent to a circle is calculated from the area of each particle of the obtained floating phase, and the above-mentioned D80, D50, and D20 are obtained.
[0047] In the levitation of the lead-free piezoelectric composition of the present embodiment, the cumulative frequency 80% particle size (D80) in the volume-based particle size distribution satisfies the above-mentioned equation (1) and also satisfies the following equation (4). By doing so, a higher mechanical quality factor Qm and a lower dielectric loss tanδ can be realized in the lead-free piezoelectric composition.
[0048]
[0049] In addition, in the levitation of the lead-free piezoelectric composition of the present embodiment, the cumulative frequency 50% particle size (D50) in the volume-based particle size distribution satisfies the above-mentioned equation (2) and also satisfies the following equation (5). By doing so, a higher mechanical quality factor Qm and a lower dielectric loss tanδ can be realized in the lead-free piezoelectric composition.
[0050]
[0051] In addition, in the levitation of the lead-free piezoelectric composition of the present embodiment, the cumulative frequency 20% particle size (D20) in the volume-based particle size distribution satisfies the above-mentioned equation (3) and also satisfies the following equation (6). By doing so, a higher mechanical quality factor Qm and a lower dielectric loss tanδ can be realized in the lead-free piezoelectric composition.
[0052]
[0053] B. Piezoelectric element :
[0054] (B-1) Composition of the piezoelectric element :
[0055] FIG. 1 is a perspective view showing the appearance of a piezoelectric element (10) related to the present embodiment. The piezoelectric element (10) comprises a piezoelectric body (20) formed from the lead-free piezoelectric composition of the present embodiment and electrodes (31, 32). The piezoelectric element (10) has a configuration in which electrodes (31, 32) are mounted on the upper and lower surfaces of a disc-shaped piezoelectric body (20). In addition, piezoelectric elements of various shapes or configurations other than this can be formed.
[0056] (B-2) Method for manufacturing a piezoelectric element :
[0057] FIG. 2 is a flowchart illustrating an example of a method for manufacturing a piezoelectric element (10). When manufacturing the piezoelectric element (10), first, a main raw material mixture of a lead-free piezoelectric composition is performed (Process T110). Here, the necessary raw material powder for the main material is selected and weighed to obtain the desired composition. The raw material powder can be an oxide, carbonate, or hydroxide of each element contained in the niobate alkali perovskite oxide constituting the main material. Specifically, K2CO3 powder, Na2CO3 powder, Li2CO3 powder, CaCO3 powder, SrCO3 powder, BaCO3 powder, Nb2O5 powder, TiO2 powder, ZrO2 powder, etc. can be preferably used. In Process T110, ethanol is added to the above-mentioned raw material powder, and a slurry is obtained by wet mixing with a ball mill, preferably for 15 hours or more. After that, the above slurry is dried to obtain a mixed powder, and the obtained mixed powder is calcined, for example, at 600 to 1000 ℃ under an atmospheric atmosphere for 1 to 10 hours to produce a columnar calcined powder (Step T120).
[0058] In addition, in the above description, a calcined powder is produced by mixing raw materials in process T110 and calcining in process T120, but it may be produced with a different composition, and for example, the operation of mixing raw material powders and calcining may be performed multiple times. Specifically, first, raw material powders containing multiple types of elements that are some of the elements included in the target alkali niobate perovskite oxide are mixed and calcined to obtain calcined powder 1. Then, with respect to the obtained calcined powder 1, raw material powders containing the remaining elements among the elements included in the target alkali niobate perovskite oxide are mixed and further calcined. In this way, a columnar calcined powder may be produced.
[0059] In addition, separate from the above-mentioned process T110, raw material mixing for the lead-free piezoelectric composition is performed (process T130). Here, the necessary raw material powder for the float is selected and weighed to obtain the desired composition. The raw material powder may be an oxide, carbonate, or hydroxide of each element included in the compound having a tungsten bronze-type structure constituting the float. Specifically, it is selected as needed from BaCO3 powder, CaCO3 powder, SrCO3 powder, Na2CO3 powder, K2CO3 powder, Nb2O5 powder, etc., and weighed. Then, ethanol is added to these raw material powders and wet-mixed using a ball mill to obtain a slurry. Wet-mixing using a ball mill is preferably carried out for 15 hours or more. After that, the above slurry is dried to obtain a mixed powder, and the obtained mixed powder is calcined at 600 to 1300°C for 1 to 10 hours under an atmospheric atmosphere, for example, to produce a floating calcined powder (Step T140). By changing the calcination temperature in Step T140, the particle size or particle size distribution of the floating calcined powder can be controlled, and as a result, the particle size or particle size distribution (D80, D50, D20, etc.) of the floating powder in the lead-free piezoelectric composition can be controlled.
[0060] After that, the columnar plastic powder obtained in Step T120 and the floating plastic powder obtained in Step T140 are each weighed, a binder and ethanol are added, and wet-mixed with a ball mill to obtain a slurry. Then, the obtained slurry is dried, granulated, and molded (Process T150). Specifically, for example, a uniaxial press is performed at a pressure of 20 MPa to form a desired shape, and for example, a CIP treatment (cold isostatic pressing) is performed on the obtained molded body at a pressure of 150 MPa. A piezoelectric element is obtained by firing the obtained CIP-pressed body at 900 to 1300°C for 5 hours in an atmospheric atmosphere (Process T160). By changing the firing temperature in this Step T160 along with the particle size and particle size distribution of the described floating plastic powder, the particle size and particle size distribution of the floating particles in the lead-free piezoelectric composition can be controlled.
[0061] Next, the piezoelectric material obtained in process T160 is cut according to the dimensional precision required for the piezoelectric element (10), and the upper and lower surfaces are processed. The piezoelectric material obtained in this way is annealed in the atmosphere at 100°C for 2 hours to stabilize its characteristics (process T170). After that, electrodes are mounted on the surface of the piezoelectric material (process T180), and polarization treatment is performed (process T190) to complete the piezoelectric element (10).
[0062] In addition, the manufacturing method described above is an example, and various other processes or processing conditions for manufacturing the piezoelectric element (10) may be used. For example, instead of separately producing the columnar and floating plastic materials in advance and then mixing and firing the powders of both, the raw materials may be mixed in proportions according to the composition of the final lead-free piezoelectric composition and then fired. However, according to the method of separately producing the columnar and floating plastic materials in advance and then mixing them, it is easier to control the composition of the columnar and floating materials more strictly, so it is possible to increase the yield of the lead-free piezoelectric composition.
[0063] C. Device applying a piezoelectric element :
[0064] The piezoelectric element (10) can be preferably used in the following devices. Examples of devices include an ultrasonic scalpel (40), an ultrasonic scaler (50), an ultrasonic cleaner (60), an ultrasonic processor (70), a piezoelectric transducer (80), an ultrasonic motor (90), a piezoelectric gyro sensor (100), a piezoelectric filter (110), and a knock sensor (120).
[0065] (C-1) Ultrasonic scalpel
[0066] FIG. 3 is a schematic diagram showing an ultrasonic scalpel (40) which is one embodiment of the present disclosure. The ultrasonic scalpel (40) is equipped with an ultrasonic vibrator (41) and an action member (43). The ultrasonic vibrator (41) has the piezoelectric element (10) and is driven to generate ultrasonic vibration when an electric signal is given. The ultrasonic vibrator (41) operates to transmit ultrasonic vibration to an action member (43) configured in an axial shape. The ultrasonic vibrator (41) drives the action member (43) so that an action of cutting, dissecting, or thermally coagulating hemostasis of biological tissue occurs near the action member (43).
[0067] (C-2) Ultrasonic scaler
[0068] FIG. 4 is a schematic diagram showing an ultrasonic scaler (50) which is one embodiment of the present disclosure. The ultrasonic scaler (50) is a dental medical device for crushing and cleaning tartar or contamination attached to the surface of teeth using ultrasonic vibrations. The ultrasonic scaler (50) is equipped with an ultrasonic vibrator (51) and a dental tip (52). The ultrasonic vibrator (51) has the piezoelectric element (10) and is driven to generate ultrasonic vibrations when an electric signal is given. The ultrasonic vibrator (51) operates to transmit ultrasonic vibrations to the dental tip (52).
[0069] (C-3) Ultrasonic cleaner
[0070] FIG. 5 is a schematic diagram showing an ultrasonic cleaner (60) which is one embodiment of the present disclosure. The ultrasonic cleaner (60) is equipped with an ultrasonic vibrator (61) and a cleaning container (63). The ultrasonic vibrator (61) has the piezoelectric element (10) and is driven to generate ultrasonic vibrations when an electric signal is given. An object to be cleaned (65) is placed in a cleaning container (63) containing a cleaning solution, and the ultrasonic vibrations generated by the ultrasonic vibrator (61) vibrating are transmitted to the cleaning solution, thereby cleaning the object to be cleaned (65).
[0071] (C-4) Ultrasonic machining machine
[0072] FIG. 6 is a schematic diagram showing an ultrasonic processing machine (70) which is one embodiment of the present disclosure. The ultrasonic processing machine (70) is equipped with a substrate (71), an ultrasonic vibrator (73), a grinding stone (75), a spindle (77), and a mounting jig (79). The substrate (71) has a disc shape, and a grinding stone (75) is formed on its outer circumference. The center of the substrate (71) is fixed to the spindle (77).
[0073] The ultrasonic vibrator (73) has the piezoelectric element (10) and is driven to generate ultrasonic vibration when an electric signal is given. The driving direction of the ultrasonic vibrator (73) is a radiating direction from the center of the substrate (71) toward the outer circumference. While generating vibration by the ultrasonic vibrator (73) and rotating the spindle (77) around its axis, the workpiece can be cut by pressing the grinding stone (75) formed on the outer circumference of the substrate (71) against the workpiece.
[0074] (C-5) Piezoelectric transducer
[0075] FIG. 7 is a schematic diagram showing a piezoelectric transducer (80) which is one embodiment of the present disclosure. The piezoelectric transducer (80) is an electromechanical energy conversion device that converts an electrical signal into mechanical displacement. The piezoelectric transducer (80) is equipped with a piezoelectric element (81). The piezoelectric element (81) has the same configuration as the piezoelectric element (10). The piezoelectric element (81) has a lead-free piezoelectric member (83) and electrodes (85, 87) mounted on both sides of the lead-free piezoelectric member (83).
[0076] (C-6) Ultrasonic motor
[0077] FIG. 8 is a schematic diagram showing an ultrasonic motor (90) which is one embodiment of the present disclosure. The ultrasonic motor (90) is equipped with an ultrasonic vibrator (91), a rotor (93), and an output shaft (95). The ultrasonic vibrator (91) has the piezoelectric element (10). The ultrasonic motor (90) is an actuator that converts the natural vibration generated by the ultrasonic vibrator (91) into rotational motion of the rotor (93) by means of frictional force. For example, when an alternating voltage is applied to the piezoelectric element (10), a bending propagating wave is generated in the ultrasonic vibrator (91), and each point on the sliding surface of the ultrasonic vibrator (91) moves in an elliptical motion. When the rotor (93) is pressed against the sliding surface of the ultrasonic vibrator (91), the rotor (93) receives frictional force from the ultrasonic vibrator (91) and rotates in the opposite direction to the bending propagating wave.
[0078] (C-7) Piezoelectric Gyro Sensor
[0079] FIG. 9 is a schematic diagram showing a piezoelectric gyro sensor (100) which is one embodiment of the present disclosure. The piezoelectric gyro sensor (100) is a device that detects angular velocity using the Coriolis force generated in a vibrator. The piezoelectric gyro sensor (100) has a lead-free piezoelectric member (101) and a piezoelectric element (107) having electrodes (103, 105) coated on both sides of the lead-free piezoelectric member (101). The piezoelectric element (107) has the same configuration as the piezoelectric element (10).
[0080] (C-8) Piezoelectric Filter
[0081] FIG. 10 is a schematic diagram showing a stacked piezoelectric filter (110) which is one embodiment of the present disclosure. The piezoelectric filter (110) is a device that excites elastic waves to extract an electrical signal of a specific frequency band. The stacked piezoelectric filter (110) has a cylindrical lead-free piezoelectric member (111) and a piezoelectric element (117) having electrodes (113, 115) on both sides of the lead-free piezoelectric member (111). The piezoelectric element (117) has the same configuration as the piezoelectric element (10).
[0082] (C-9) Knock sensor
[0083] FIG. 11 is a schematic diagram of a knock sensor (120) which is one embodiment of the present disclosure. The knock sensor (120) is a device that detects knocking by converting a force applied by vibration of the engine block caused by knocking into an electrical signal, for example, and is used by mounting it on an engine block. The knock sensor (120) has a piezoelectric element (127) having a lead-free piezoelectric member (121) and electrodes (123, 125). The piezoelectric element (127) has the same configuration as the piezoelectric element (10).
[0084] According to the lead-free piezoelectric composition of the present embodiment configured as described above, in a lead-free piezoelectric composition having a column made of alkaline niobate perovskite oxide, by providing a float comprising a compound having the described tungsten bronze-type structure, the sinterability is increased, and at least one of the three conditions shown in equations (1) to (3) regarding D80, D50, and D20 related to the particle size of the float is satisfied, thereby increasing the mechanical quality factor Qm in the lead-free piezoelectric composition and reducing the dielectric loss tanδ.
[0085] Examples
[0086] Twenty-seven types of lead-free piezoelectric compositions, samples S1 to S27, with different compositions related to the columnar and float phases, were fabricated, and evaluations regarding the mechanical quality factor Qm and dielectric loss tanδ were performed.
[0087] FIGS. 12 to 14 are explanatory diagrams summarizing the composition and evaluation results of each fabricated sample. FIG. 15 is an explanatory diagram showing the composition of the main phase of each sample. FIG. 16 is an explanatory diagram regarding the flotation plastic component for forming the flotation of each sample.
[0088] <Production of Lead-Free Piezoelectric Composition>
[0089] [Sample S1]
[0090] As Sample S1, a lead-free piezoelectric composition composed of a columnar structure and not having a floating structure was prepared. In FIG. 2, the process T110, which involves mixing the raw material powder of the columnar structure, and the process T120, which involves calcining the mixed raw material, were described in order to produce the calcined powder constituting the columnar structure. However, in this case, a portion of the raw material powder of the columnar structure was mixed and calcined to produce calcined powder 1, and then the remaining raw material powder was mixed with calcined powder 1 and calcined to produce calcined powder 2 as the columnar calcined powder. When producing calcined powder 1, K2CO3 powder, Na2CO3 powder, and Nb2O5 powder were used as raw material powders and weighed according to the "Composition of Calcined Powder 1" shown in FIG. 15. Ethanol was added to the weighed raw material powders, and wet mixing was performed using a ball mill for 15 hours to obtain a slurry. Afterwards, the mixed powder obtained by drying the slurry was calcined at 600 to 1100°C for 1 to 10 hours in an atmospheric environment, and calcined powder 1 was obtained.
[0091] To the obtained calcined powder 1, an additive having the composition shown as the additive of sample S1 in FIG. 15 was added in the ratio shown in FIG. 15. Here, the amount of the additive shown in FIG. 15 is expressed as a relative amount when the calcined powder 1 to be added is 100 mol%. Then, ethanol was added to the raw powder to which the additive was added, and a slurry was obtained by wet mixing in a ball mill for 15 hours. Afterward, the mixed powder obtained by drying the slurry was calcined at 600 to 1100 °C for 1 to 10 hours under an atmospheric atmosphere to obtain calcined powder 2, which is a columnar calcined powder.
[0092] Ethanol and a binder were added to plastic powder 2 and wet-mixed using a ball mill to obtain a slurry. Subsequently, the slurry was dried, granulated, and molded into a desired shape by uniaxial pressing at a pressure of 20 MPa. Afterward, a molded body was obtained by performing CIP treatment at a pressure of 150 MPa (corresponding to process T150). The obtained molded body was fired in an atmospheric atmosphere at 900°C to 1300°C for 1 to 10 hours (corresponding to process T160) to produce the lead-free piezoelectric composition (piezoelectric element) of sample S1. The composition of the columnar phase of sample S1 obtained in this way is shown in FIG. 15. In addition, the columnar phase constituting sample S1 and samples S2 to S24 described later is also referred to as "columnar phase A" (see FIG. 12 to 15).
[0093] [Samples S2 ~ S7]
[0094] As samples S2 to S7, together with having the same column (column A) as sample S1, Ba2KNb5O 15 A lead-free piezoelectric composition was prepared having a float comprising a compound having a tungsten bronze-type structure represented by (see FIG. 12). The plastic powder for forming the columnar structure was prepared in the same way as plastic powder 2 described in sample S1.
[0095] To produce samples S2 to S7, BaCO3 powder, K2CO3 powder, and Nb2O5 powder were weighed according to the composition of the floating powder described above. Then, ethanol was added to these raw powders and wet-mixed in a ball mill for 15 hours to obtain a slurry. Afterward, the slurry was dried to obtain a mixed powder, and the obtained mixed powder was calcined in an atmospheric atmosphere at 600 to 1300 °C for 1 to 10 hours to produce floating calcined powder (Step T140). Afterward, the columnar calcined powder 2 described above and the floating calcined powder were each weighed, a binder and ethanol were added, and wet-mixed in a ball mill to obtain a slurry. Afterward, the obtained slurry was dried, granulated, and subjected to a uniaxial press at a pressure of 20 MPa to form a desired shape. Afterwards, a molded body was obtained by performing CIP treatment at a pressure of 150 MPa (Process T150). The obtained molded body was fired at 900 °C to 1300 °C for 1 to 10 hours in an atmospheric atmosphere (Process T160), and a piezoelectric material was produced as a lead-free piezoelectric composition of samples S2 to S7. In addition, the content ratio (volume%) of the floating material in samples S2 to S7 was standardized to 1.5 volume%.
[0096] Here, for samples S2 to S7, the particle size distribution of the floating plastic powder was changed by changing the plasticizing temperature in process T140, and the particle size distribution of the floating material in the lead-free piezoelectric composition was also changed by changing the firing temperature in process T160. Specifically, samples S2 to S5 were fabricated using plastic powder (D20=0.05 μm, D50=0.2 μm, D80=0.5 μm) plasticized at the same plasticizing temperature, and samples S6 and S7 were fabricated using plastic powder (D20=15 μm, D50=30 μm, D80=80 μm) plasticized at a different plasticizing temperature from samples S2 to S5 (see FIG. 16). The floating calcined powder used in samples S2 to S5 is also referred to as "calcined powder α," and the floating calcined powder used in samples S6 and S7 is also referred to as "calcined powder β." In addition, the particle size of the floating calcined powder used in each sample shown in FIG. 16 was measured using a laser diffraction / scattering particle size distribution measuring device (manufactured by Horiba Corporation, LA-750). Also, in process T160, the calcination temperature shown in FIG. 16 was adopted for each of samples S2 to S7.
[0097] [Samples S8 ~ S12]
[0098] As samples S8 to S12, lead-free piezoelectric compositions (piezoelectric materials) were produced having a column (column A) identical to that of sample S2, and a composition of a compound having a tungsten bronze-type structure constituting the float that is different from that of sample S2 (see FIG. 12). When producing sample S8, BaCO3 powder, SrCO3 powder, K2CO3 powder, and Nb2O5 powder were used as raw materials for the float. When producing sample S9, BaCO3 powder, CaCO3 powder, K2CO3 powder, and Nb2O5 powder were used as raw materials for the float. When producing sample S10, SrCO3 powder, Na2CO3 powder, and Nb2O5 powder were used as raw materials for the float. When producing sample S11, BaCO3 powder, Na2CO3 powder, and Nb2O5 powder were used as raw materials for the float. When preparing Sample S12, BaCO3 powder, Na2CO3 powder, K2CO3 powder, and Nb2O5 powder were used as raw materials for the floating powder. Then, for each of Samples S8 to S12, floating powder with the composition and particle size shown in Fig. 16 was prepared. Samples S8 to S12 were prepared under the same conditions as Sample S2, except that the composition of the floating powder was different. For Samples S8 to S12 as well, the floating content ratio (volume%) was standardized to 1.5 volume%.
[0099] [Samples S13 ~ S19]
[0100] As samples S13 to S19, lead-free piezoelectric compositions (piezoelectrics) were produced that have the same columnar phase (columnar phase A) as sample S2, and the composition of the compound having a tungsten bronze-type structure constituting the float is the same as sample S2, but the particle size of the plastic powder of the float is different from that of sample S2 (see FIG. 12 and FIG. 16). For samples S13 to S19, the particle size distribution of the plastic powder used to form the float was adjusted by classifying the plastic powder β used in samples S6 and S7. Samples S13 to S19 were produced under the same conditions as sample S2, except that the particle size distribution of the plastic powder of the float is different and the firing temperature of process T160 is 1150 °C. In samples S13 to S19 as well, the content ratio (volume%) of the float was standardized to 1.5 volume%.
[0101] [Samples S20 ~ S24]
[0102] Lead-free piezoelectric compositions (piezoelectrics) were produced as samples S20 to S24, which have a column (column A) identical to sample S2 and a float of the same composition as sample S2 formed using plasticizing agent α, but with different float content ratios (see FIG. 13 and FIG. 16). The float content ratio (volume %) in samples S20 to S24 is shown as "float amount" in FIG. 13. Samples S20 to S24 were produced under the same conditions as sample S2.
[0103] [Samples S25 ~ S27]
[0104] As samples S25 to S27, lead-free piezoelectric compositions (piezoelectrics) were produced having the same float as sample S2, but with a columnar composition different from sample S2 (see FIG. 15 and FIG. 16). As shown in FIG. 15, samples S25 to S27 used the same plastic powder 1 as sample S2 when producing the columnar plastic powder, but the type and ratio of additives added to plastic powder 1 to produce plastic powder 2 were different, and as a result, the composition of the columnar powder was different. Samples S25 to S27 were produced under the same conditions as sample S2, except that the type and ratio of additives added to plastic powder 1 were different. In samples S25 to S27 as well, the content ratio (volume%) of the float was standardized to 1.5 volume%.
[0105] <Evaluation Method for Mechanical Quality Factor Qm and Dielectric Loss tanδ>
[0106] For each sample, measurements were performed using an impedance analyzer (Keysight Technologies, E4990A) to calculate tanδ at room temperature and 1 kHz. Additionally, the mechanical quality factor Qm was determined by the resonance-anti-resonance method. The mechanical quality factor Qm was evaluated as “○” if the value was 500 or greater, “△” if it was 200 or greater but less than 500, and “×” if it was less than 200 (see Figs. 12–14). The dielectric loss tanδ was evaluated as “○” if the dielectric loss tanδ was 1.0% or less, “△” if it was greater than 1.0% and 2.5% or less, and “×” if it was greater than 2.5% (see Figs. 12–14).
[0107] <Method for Calculating Particle Size and Floating Amount (Volume %)>
[0108] After mirror polishing the sintered bodies of each sample and performing a conductive treatment, back-field electron images were captured at magnifications of 500 to 3000 using an electron probe micro analyzer (EPMA). At this time, the obtained back-field electron images were binarized using image analysis software to classify them into columnar and floating phases. Then, the original particle diameter was calculated from the area of each particle in the obtained floating phase, and D80, D50, and D20 were obtained (see FIGS. 12 to 14). In addition, after classifying the back-field electron images into columnar and floating phases by binarizing them using image analysis software as described above, the amount of floating phase (volume%) was calculated from the area ratio of the obtained columnar and floating phases.
[0109] <Method of Interpreting Each Image>
[0110] The elemental ratios of the main phase and the floating phase in each sample were measured using EPMA-WDS (wavelength dispersive X-ray spectroscopy) and EPMA-EDS (energy dispersive X-ray spectroscopy). In addition, whether the floating phase of each sample was a tungsten bronze-type compound was determined by performing Rietveld analysis using the diffraction results of powder X-ray diffraction (XRD).
[0111] <Evaluation Results>
[0112] In Figures 12 to 14, the results of the comprehensive evaluation of each sample are shown in the "Judgment" column. If at least one of the evaluation results of the mechanical quality factor Qm and the dielectric loss tanδ of each sample is "×", the comprehensive evaluation is labeled "×". Among the remaining samples for which the comprehensive evaluation is not "×", if at least one of the evaluation results of the mechanical quality factor Qm and the dielectric loss tanδ is "△", the comprehensive evaluation is labeled "△". Additionally, for the remaining samples, that is, samples for which both the evaluation results of the mechanical quality factor Qm and the dielectric loss tanδ are "○", the comprehensive evaluation is labeled "○".
[0113] As shown in FIGS. 12 to 14, it was confirmed that a lead-free piezoelectric composition comprises a columnar phase consisting of an alkali niobate perovskite oxide and a float comprising a compound having a tungsten bronze-type structure including Nb and at least one selected from Ba, Ca, Sr, Na, and K, and by satisfying at least one of the three conditions described in equations (1) to (3) regarding D80, D50, and D20 related to the particle size distribution of the float, the effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is obtained (comparison between samples S2-S6 and S8-S27 and samples S1 and S7). The Equation 2.01. 2.01. 2.01. 1.21. 2.12. 2.0. 2.0. 2.0.1.1.2. 2.0. 2.0. 2. 2. 2. 2. 2.2. 2.2. 2.2. 2.2. 2.4. 2.2. 2.1. 2.0. 2.1
[0114] Specifically, it was confirmed that the effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is obtained in samples S2-S6, in which all of D80, D50, and D20 related to the particle size distribution of the fuse satisfy equations (1)-(3), as well as in samples S13-S19, in which at least one of D80, D50, and D20 satisfies equations (1)-(3), compared to sample S7, in which all of D80, D50, and D20 do not satisfy equations (1)-(3). In addition, in FIGS. 12-14, when each of D80, D50, and D20 does not satisfy the described equations (1)-(3), hatching is applied to show them.
[0115] In addition, as shown in samples S8-S12, it was confirmed that if the conditions shown in the above-mentioned equations (1)-(3) related to the float are satisfied, the same effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is obtained even if the composition of the float is varied. In addition, as shown in samples S20-S24, it was confirmed that the same effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is obtained even if the content ratio of the float is varied in the range of, for example, 0.5-10.0 volume% (see FIG. 13). In particular, it was confirmed that the effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is enhanced by setting the content ratio of the float to 0.5-7.0 volume%. In addition, as shown in samples S2 and S25-S27, it was confirmed that the same effect of increasing the mechanical quality factor Qm and reducing the dielectric loss tanδ is obtained even when the composition of the alkali niobate perovskite oxide, which forms a columnar phase and exhibits piezoelectricity, is varied (see Fig. 14).
[0116] The present disclosure is not limited to the embodiments described above, and can be realized in various configurations within the scope that does not deviate from the intent thereof. For example, technical features in embodiments corresponding to technical features in each form described in the summary of the invention may be appropriately substituted or combined to solve some or all of the problems described above, or to achieve some or all of the effects described above. Furthermore, if such technical features are not described as essential in this specification, they may be appropriately deleted.
[0117] The present disclosure can also be realized in the following forms.
[0118] [Application Example 1]
[0119] As a lead-free piezoelectric composition,
[0120] A columnar phase composed of alkaline niobate perovskite oxide, and
[0121] A flotation comprising a compound having a tungsten bronze-type structure comprising niobium (Nb) and at least one selected from barium (Ba), calcium (Ca), strontium (Sr), sodium (Na), and potassium (K).
[0122] Equipped with,
[0123] The above-mentioned lead-free piezoelectric composition is characterized by satisfying at least one of the three conditions shown in the following equations (1) to (3) regarding the cumulative frequency of 80% particle size (D80), 50% particle size (D50), and 20% particle size (D20) in the particle size distribution based on volume.
[0124]
[0125] [Application Example 2]
[0126] As a lead-free piezoelectric composition as described in Application Example 1,
[0127] In the above-mentioned case, the cumulative frequency 80% particle size (D80) in the volume-based particle size distribution satisfies the above equation (1) and also satisfies the following equation (4).
[0128] Lead-free piezoelectric composition.
[0129]
[0130] [Application Example 3]
[0131] As a lead-free piezoelectric composition as described in Application Example 1 or 2,
[0132] In the above-mentioned case, the cumulative frequency 50% particle size (D50) in the volume-based particle size distribution satisfies the above equation (2) and also satisfies the following equation (5).
[0133] Lead-free piezoelectric composition.
[0134]
[0135] [Application Example 4]
[0136] As a lead-free piezoelectric composition as described in any one of Application Examples 1 to 3,
[0137] In the above-mentioned case, the cumulative frequency 20% particle size (D20) in the volume-based particle size distribution satisfies the above equation (3) and also satisfies the following equation (6).
[0138] Lead-free piezoelectric composition.
[0139]
[0140] [Application Example 5]
[0141] As a lead-free piezoelectric composition as described in any one of Application Examples 1 to 4,
[0142] The alkali niobate-based perovskite-type oxide constituting the above column is characterized by containing manganese (Mn).
[0143] Lead-free piezoelectric composition.
[0144] [Application Example 6]
[0145] As a lead-free piezoelectric composition as described in any one of Application Examples 1 to 5,
[0146] The alkali niobate-based perovskite-type oxide constituting the above column is,
[0147] Cho Seong-sik (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 )O 3+e(wherein element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, and Sr, element M2 is at least one of Ti and Zr, satisfying 0<a<1, 0<b<1, a+b=1, c is 0.80<c<1.10, 0<d1<1, 0<d2<1, 0<d3<1, d1+d2+d3=1, and e is a value indicating oxygen deficiency or excess), comprising a columnar phase composed of an alkali niobate perovskite-type oxide
[0148]
[0149] Characterized by satisfying
[0150] Lead-free piezoelectric composition.
[0151] [Application Example 7]
[0152] A piezoelectric element formed by a lead-free piezoelectric composition as described in any one of Application Examples 1 to 6, and
[0153] electrode mounted on the above piezoelectric element
[0154] A piezoelectric element characterized by having
[0155] [Application Example 8]
[0156] A device characterized by having a piezoelectric element as described in Application Example 7.
[0157] [Application Example 9]
[0158] As a device described in Application Example 8,
[0159] The above device is characterized by being any one of an ultrasonic scalpel, an ultrasonic scaler, an ultrasonic cleaner, an ultrasonic processing machine, a piezoelectric transducer, an ultrasonic motor, a piezoelectric gyro sensor, a piezoelectric filter, and a knock sensor. Explanation of the symbols
[0160] 10: Piezoelectric element 20: Piezoelectric element 31, 32: Electrodes 40: Ultrasonic scalpel 41: Ultrasonic transducer 43 : Absence of action 50: Ultrasonic scaler 51: Ultrasonic transducer 52 : Dental Tips 60 : Ultrasonic cleaner 61: Ultrasonic transducer 63 : Cleaning container 65 : Washing material 70 : Ultrasonic machining machine 71 : Entry 73: Ultrasonic transducer 75 : Jiseokbu 77 : Spindle 79: Mounting Jig 80: Piezoelectric transducer 81: Piezoelectric element 83 : Lead-free piezoelectric element 85 : Electrode 90: Ultrasonic motor 91: Ultrasonic transducer 93 : Rotor 95 : Output axis 100 : Piezoelectric gyro sensor 101 : Lead-free piezoelectric element 103 : Electrode 107 : Piezoelectric element 110: Piezoelectric filter 111 : Lead-free piezoelectric element 113 : Electrode 117 : Piezoelectric element 120 : Knock sensor 121 : Lead-free piezoelectric element 123 : Electrode 127 : Piezoelectric element
Claims
Claim 1 A lead-free piezoelectric composition comprising a column made of an alkaline niobate perovskite oxide and a float comprising a compound having a tungsten bronze-type structure including at least one selected from niobium (Nb), barium (Ba), calcium (Ca), strontium (Sr), sodium (Na), and potassium (K), wherein the float satisfies at least one of the three conditions shown in the following equations (1) to (3) regarding cumulative frequency 80% particle size (D80), cumulative frequency 50% particle size (D50), and cumulative frequency 20% particle size (D20) in a volume-based particle size distribution. Claim 2 A lead-free piezoelectric composition characterized in that, in the above-mentioned float, the cumulative frequency 80% particle size (D80) in the particle size distribution based on volume satisfies the above equation (1) and also satisfies the following equation (4). Claim 3 A lead-free piezoelectric composition characterized in that, in the above-mentioned float, the cumulative frequency 50% particle size (D50) in the volume-based particle size distribution satisfies the above equation (2) and also satisfies the following equation (5). Claim 4 A lead-free piezoelectric composition characterized in that, in the above-mentioned float, the cumulative frequency 20% particle size (D20) in the volume-based particle size distribution satisfies the above equation (3) and also satisfies the following equation (6). Claim 5 A lead-free piezoelectric composition according to claim 1, wherein the alkali niobate-based perovskite-type oxide constituting the column comprises manganese (Mn). Claim 6 In claim 1, the niobate alkali-based perovskite-type oxide constituting the above column is of the compositional formula (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 )O 3+e (wherein element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, and Sr, element M2 is at least one of Ti and Zr, satisfying 0<a<1, 0<b<1, a+b=1, c is 0.80<c<1.10, 0<d1<1, 0<d2<1, 0<d3<1, d1+d2+d3=1, and e is a value indicating oxygen deficiency or excess), comprising a columnar phase composed of an alkali niobate perovskite-type oxide A lead-free piezoelectric composition characterized by satisfying [condition]. Claim 7 A piezoelectric element characterized by having a piezoelectric body formed by a lead-free piezoelectric composition described in any one of claims 1 to 6, and an electrode mounted on said piezoelectric body. Claim 8 A device characterized by having a piezoelectric element as described in claim 7. Claim 9 In claim 8, the device is characterized as being any one of an ultrasonic scalpel, an ultrasonic scaler, an ultrasonic cleaner, an ultrasonic processing machine, a piezoelectric transducer, an ultrasonic motor, a piezoelectric gyro sensor, a piezoelectric filter, and a knock sensor.
Citation Information
Patent Citations
Piezoelectric element and method for manufacturing piezoelectric element
KR1020230110810A
